EXPANSION OF PARKING AREA USING RIGID PAVEMENT AT COL. ROBERT ATTY BESSING MALINAU AIRPORT - Octaviano Hindarto, Donni; Winiasri , Linda; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The increasing number of passengers at Colonel Robert Atty Bessing Airport in Malinau, North Kalimantan, has led to parking shortages, with the existing facility accommodating only 28 vehicles. This study aims to plan the expansion of parking facilities using rigid pavement to ensure capacity, durability, and serviceability. Passenger forecasts up to 2035 were conducted using the Holt Linear Trend method, while parking demand was estimated based on forecasted passengers, vehicle ratios, and peak-hour factors. Several layout alternatives were compared to maximize land efficiency. Pavement design followed Manual Desain Perkerasan Jalan No. 03/M/BM/2024, considering traffic load (JSKN), soil strength (CBR 8.88%), and concrete strength (K-300). The results show that by 2035 parking demand will reach 130 vehicles, requiring approximately 6,000 m² of land. The 90° layout was selected as the most efficient option for maximizing capacity. The recommended pavement structure consists of a 20 cm reinforced concrete slab supported by a 15 cm lean concrete subbase. This research provides practical recommendations for sustainable airport landside planning, ensuring that parking facilities can meet long-term demand with durable construction.